2019
DOI: 10.1186/s40035-019-0157-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and genetic spectrum in Chinese patients with recessive hereditary spastic paraplegia

Abstract: Background Although many causative genes of hereditary spastic paraplegia (HSP) have been uncovered in recent years, there are still approximately 50% of HSP patients without genetically diagnosis, especially in autosomal recessive (AR) HSP patients. Rare studies have been performed to determine the genetic spectrum and clinical profiles of recessive HSP patients in the Chinese population. Methods In this study, we investigated 24 Chinese index AR/sporadic patients by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 50 publications
5
29
0
Order By: Relevance
“…In the current study, HTS analysis of 240 HSP families identified six additional autosomal-recessive HSP families, with eight patients carrying six homozygous or compound heterozygous variants of CAPN1. Among them, the three homozygous variants (c.182_183insC (p.V64Gfs*103) in Families 1 and 4, c.759+1G>A in Family 3, and c.853C>T (p.R285*) in Family 5) were found to be known truncating mutations, 6,11,21 while the three compound heterozygous variants ((c.1442G>A (p.R481Q) in Family 6, c.1493C>T (p.P498L) in Families 2 and 6, and c.1852C> T (p.R618W) in Family 2) were defined as novel, likely-pathogenic missense mutations. A combined total of 33 rare CAPN1 mutations were detected between our cohort and previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, HTS analysis of 240 HSP families identified six additional autosomal-recessive HSP families, with eight patients carrying six homozygous or compound heterozygous variants of CAPN1. Among them, the three homozygous variants (c.182_183insC (p.V64Gfs*103) in Families 1 and 4, c.759+1G>A in Family 3, and c.853C>T (p.R285*) in Family 5) were found to be known truncating mutations, 6,11,21 while the three compound heterozygous variants ((c.1442G>A (p.R481Q) in Family 6, c.1493C>T (p.P498L) in Families 2 and 6, and c.1852C> T (p.R618W) in Family 2) were defined as novel, likely-pathogenic missense mutations. A combined total of 33 rare CAPN1 mutations were detected between our cohort and previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…A combined total of 33 rare CAPN1 mutations were detected between our cohort and previously reported cases. 5,6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Notably, seven mutations (c.182_183insC, c.759+1G>A, c.853C>T, c.1015C>T, c.1142C>T, c.1176G>A, and c.1534C>T) were shared in ≥2 pedigrees, and in particular the nonsense mutation c.1176G>A (p.W392*) was most prevalent, recorded in four pedigrees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently performed comprehensive genetic investigations in Chinese HSP patients and also found that SPG4 and SPG11 were the most frequent form of AD-HSP and AR-HSP in southeast China, respectively (4,5). However, there are still very few reports on genetic analysis of HSP patients in central-southern China.…”
Section: Introductionmentioning
confidence: 99%